Counter-enclose, produce and resist. The defense of the common goods in two peasant communities (Argentina) - Gómez Herrera, Andrea Geanina (2018)
The various manifestations of resistance against the plundering of common goods are the other side of the capitalist enclosures. These expressions of collective actions encompass a broad battery of strategies on the part of rural communities. Many of these manifestations could be interpreted ascounter-enclosure (physical or institutional).In this context, we ask ourselves what are the modalities that assume peasant struggles which set new borders for the control of common goods in Santiago del Estero (NW Argentina).To answer this question, we address two cases: the design of a peasant reserve in Ojo de Agua and the community livestock enclosure of El Hoyo. The origins of both experiences are linked to conflicts over land and the interventions of state agents.The argumentation is structured from the data constructed during the fieldwork that included observation records and conducting in-depth interviews. This allowed toexplore the repertoire of collective action, of readjustment of current legislation and re-functionalization of resources arising from state programs. Likewise, we present evidence of how everyday policies operate around control of the Commons and the tensions that go through these processes.